Experimental evaluation of long- and short-term moisture damage characteristics of asphalt mixtures. Issue 1 (2nd January 2016) - Varveri, Aikaterini; Avgerinopoulos, Stavros; Scarpas, Athanasios
Abstract : Moisture damage susceptibility was evaluated using a conditioning protocol, which comprises two conditioning types, namely bath immersion and pore pressure application. The protocol was used to quantify the effect of long- and short-term moisture damage processes on asphalt mixtures. In addition, computed tomography scanning and image analysis techniques were employed to characterise damage due to pore pressure. Compacted porous asphalt samples, with various aggregate and bitumen types, were conditioned by combinations of water immersion and cyclic pore pressures by means of the moisture-induced sensitivity tester, and subsequently tested using the indirect tensile test. The results indicated that strength degradation due to moisture is influenced by the conditioning regime and time, as well as by aggregate and binder types. Overall, asphalt mixtures with polymer-modified bitumen and sandstone aggregates exhibited the best performance against moisture. Nevertheless, the long- and short-term moisture damage mechanisms had a diverse effect on mixture degradation. Repeated pore pressures were found to have a significant effect on mixture tensile strength. Image analysis revealed the effect of pore pressures on air voids content and interconnectivity of asphalt mixtures, while visual observations suggested that repeated pore pressures induce damage by opening new flow paths and eroding fine sand and mastic particles.